Redox-Induced Spin-State Switching and Mixed Valency in Quinonoid-Bridged Dicobalt Complexes - Schweinfurth, David; Rechkemmer, Yvonne; Hohloch, Stephan; Deibel, Naina; Peremykin, Irina; Fiedler, Jan; Marx, Raphael; Neugebauer, Petr; van Slageren, Joris; Sarkar, Biprajit (Chemistry : a European journal, 2014)
The complexes [{(tmpa)CoII}2(μ‐L1)2−]2+ (12+) and [{(tmpa)CoII}2(μ‐L2)2−]2+ (22+), with tmpa=tris(2‐pyridylmethyl)amine, H2L1=2,5‐di‐[2‐(methoxy)‐anilino]‐1,4‐benzoquinone, and H2L2=2,5‐di‐[2‐(trifluoromethyl)‐anilino]‐1,4‐benzoquinone, were synthesized and characterized. Structural analysis of 22+ revealed a distorted octahedral coordination around the cobalt centers, and cobalt–ligand bond lengths that match with high‐spin CoII centers. Superconducting quantum interference device (SQUID) magnetometric studies on 12+ and 22+ are consistent with the presence of two weakly exchange‐coupled high‐spin cobalt(II) ions, for which the nature of the coupling appears to depend on the substituents on the bridging ligand, being antiferromagnetic for 12+ and ferromagnetic for 22+. Both complexes exhibit several one‐electron redox steps, and these were investigated with cyclic voltammetry and UV/Vis/near‐IR spectroelectrochemistry. For 12+, it was possible to chemically isolate the pure forms of both the one‐electron oxidized mixed‐valent 13+ and the two‐electron oxidized isovalent 14+ forms, and characterize them structurally as well as magnetically. This series thus provided an opportunity to investigate the effect of reversible electron transfers on the total spin‐state of the molecule. In contrast to 22+, for 14+ the metal–ligand distances and the distances within the quinonoid ligand point to the existence of two low‐spin CoIII centers, thus showing the innocence of the quintessential non‐innocent ligands L. Magnetic data corroborate these observations by showing the decrease of the magnetic moment by roughly half (neglecting spin exchange effects) on oxidizing the molecules with one electron, and the disappearance of a paramagnetic response upon two‐electron oxidation, which confirms the change in spin state associated with the electron‐transfer steps. Innocent until proven guilty! Reversible redox‐induced spin‐state changes have been observed in quinonoid‐bridged dicobalt complexes, in which the quintessential non‐innocent quinonoid ligands have been proven to be innocent (see figure; hs=high spin, ls=low spin).